Parental mediation: Its impact on contexts of emotional behavioral adjustment among children in Kota Kinabalu district - Ling, C.; Hon, Kai Yee (Cogent OA, 2021)
The current study aimed to examine the impact of parental mediation on the contexts of emotional behavioral adjustment among 9-to-11-year-old children in Kota Kinabalu, Sabah. A random sampling of 175 parents was recruited to participate in the study using the Google forms online questionnaire. Multiple regression analysis indicated the significance in monitoring influence on the context of conduct problems, F(1, 173) = 4.666; hyperactivity, F(1, 173) = 13.203; prosocial behavior, F(2, 172) = 13.542; p < .05, with respect to the subscales of Strengths and Difficulties Questionnaire (SDQ). While active co-use influences on the peer problem F(1, 173) = 7.496; and prosocial behavior F(2, 172) = 13.542, p < .05. Interaction and technical restriction, however, did not show any significant influence. Findings thus suggested that monitoring and active co-use have a positive effect on the prosocial behavior while diminishing the other subscales of SDQ. © 2021 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.